Road to reading : a program for preventing and remediating reading difficulties - Blachman, Benita A. (Paul H. Brookes Pub. Co., 2008)
Covers sound-symbol correspondences, decoding skills, reading out loud, phonetically regular words and high frequency words, and dictation.